Development of an ADDIE-Based Problem-Solving Skills Module to Enhance OPPD Administrators’ Independence - Mohammad Khair Alfikry; Faisal Sundani Kamaluddin; Achmad Ushuluddin (FKIP - Universitas Riau, 2026)
This study aimed to develop and examine the effectiveness of a problem-solving skills module based on the ADDIE model to enhance the independence of the female board members of the Darussalam Islamic Boarding School Student Organization (OPPD) at Darussalam Islamic Boarding School, Garut. The research employed a Research and Development (R&D) method using the ADDIE stages: Analyze, Design, Develop, Implement, and Evaluate. The developed module was contextual, practical, and integrated with Islamic boarding school values. Content validity was assessed using Aiken’s V index, yielding coefficients ranging from 0.93 to 0.96, indicating very high validity. Effectiveness was tested through a one-group pretest–posttest design using a social independence scale and involving 40 participants. Data were analyzed using the Shapiro-Wilk normality test, paired t-test, N-Gain, and Cohen’s d effect size. The results revealed a significant improvement in students’ independence after training (t (39) = -7.629, α < 0.05), with the mean score improving from 80.28 to 89.55. The N-Gain was 0.44 (moderate effectiveness category) while Cohen’s d reached 1.66, indicating a very large effect. Therefore, the module may serve as a practical instructional model for developing organizational autonomy and leadership competence in Islamic boarding school student organizations.